Relaciones laborales en la España del primer tercio del siglo XX. Una reflexión sociológica - García Calavia, Miguel Ángel (Cuadernos de Relaciones Laborales, 2011)
In this text we explore the first theoretical systematizations in Spain of employment regulation which took place at the beginning of the 20th century, focusing on the aspects considered to be important in them, the conceptions or arguments of their authors, their intellectual origins and the contributions they made. In Spain, very little analysis of this type has been carried out. The text addresses, first, criticisms of the regulation of relations between employers and workers as privately constituted; second, the systematization of social policies; third, proposals for a new social constitution; and finally, trade union alternatives to face the growing tendency toward the concentration of capital (with all its consequences).